GROUNDWATER AVAILABILITY AND AQUIFER PROPERTIES IN JIGAWA STATE: A GIS AND REMOTE SENSING APPROACH - Mallam, Ibrahim; Amoo, Afeez O.; Umar, D. A.; Usman, S. U.; Gebbe, H. M. (FUDMA JOURNAL OF SCIENCES, 2025)
Globally, disparities in groundwater availability pose significant challenges for rural communities, particularly in semi-arid regions, where agriculture is predominant and water access is limited by both hydrogeological and climatic constraints. The aim of this study is to assess groundwater availability and aquifer properties using an integrated Geographic Information System (GIS) and Remote Sensing (RS) approach across diverse geological formations, including the Precambrian Basement Complex and the Quaternary Chad Formation. Field data from 30 sampling stations, including static water levels (SWL), porosity, specific yield, and hydraulic conductivity, were collected and integrated with thematic maps (geology, topography, lineament density) derived from Landsat ETM+ imagery (2003) and 30 m SRTM DEMs using ArcGIS 9.3 and the Analytical Hierarchy Process (AHP) with weighted overlay analysis. Statistical analysis, including a student’s t-test, revealed significant seasonal SWL declines in the Basement Complex (p = 0.021) but stability in the Chad Formation (p = 0.278), reflecting recharge variations. The resulting Groundwater Potential Zones (GWPZ) map classified 28.5% of the state as high potential, 29% as moderate, and 42.5% as low, validated by a strong R2 of 0.81 with borehole yields. Results indicate higher groundwater potential in the Chad Formation (27.9% specific yield in Tashena, Birniwa) compared to the Basement Complex (5.3% in Jada, Roni). This study provides a scalable framework for water resource management, highlighting the Chad Formation’s suitability for irrigation and the need for targeted interventions in the Basement Complex, despite limitations from outdated 2003 imagery. Future research should focus on long-term recharge monitoring to ensure...